Palms, T'dad - (:unkn) unknown (My University, 2009)
A picture of coconut trees growing close to the waters edge.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Coasts--Trinidad and Tobago; Shorelines--Trinidad and Tobago; Bodies of water--Trinidad and Tobago; Islands--Trinidad and Tobago